(untitled) - Rapp, Donald (Berlin, 2008)
In ASSESSING CLIMATE CHANGE Donald Rapp has investigated a large body of scientific data relevant to climate change, approaching each element with necessary (but neutral) scientific skepticism. The chapters of the book attempt to answer a number of essential questions in relation to global warming and climate change. He begins by showing how the earth s climate has varied in the past, discussing ice ages, the Holocene period since the end of the last ice age, particularly during the past 1000 years. He investigates the reliability of "proxies" for historical temperatures and assesses the hockey stick version of global temperatures for the past millennium. To do this effectively he looks carefully at how well near surface temperatures of land and ocean on earth have been monitored during the past 100 years or more, and looks at the utility and significance of a single global average temperature.
Keywords: Climatic changes,Earth temperature,Global temperature changes